Dehydration, Hyperhydration, and Hyponatremia in Tropical Climates - Aragón Vargas, Luis Fernando (2010)
Six statements are presented with supporting data: (1) An important number of athletes train and compete in hot and humid conditions that impair their performance; (2) dehydration should be avoided when exercising in the heat; (3) many athletes arrive hypohydrated for their workouts or competitions; (4) complete rehydration is possible for some individuals; (5) quick post-exercise rehydration remains a challenge; and (6) exercise-associated hyponatremia is not likely to happen in the heat.